Management of neuroendocrine neoplasms: conformity with guidelines in and outside a center of excellence. Issue 6 (15th June 2022) - Morin, Carole; Benedetto, Keo-Morakort; Deville, Agathe; Milot, Laurent; Theillaumas, Aurélie; Hervieu, Valérie; Pioche, Mathieu; Poncet, Gilles; Forestier, Julien; François, Laurent; Borson-Chazot, Francoise; Adham, Mustapha; et al.
Abstract : Purpose: To improve neuroendocrine neoplasm (NEN) management, the European Neuroendocrine Tumor Society (ENETS) recognised 62 Centers of Excellence (CoE). This retrospective study compares conformity of patients' initial management within vs outside an ENETS CoE with clinical practice guidelines (CPGs). Methods: Patients diagnosed with a NEN between August 2018 and July 2020 and presented in the Lyon-CoE Multidisciplinary Tumour Board (MDT) were included. Factors potentially associated with the conformity of initial management (work-up and first treatment) to CPG underwent univariate and multivariate analyses. Results: Among the 615 included patients, 170 (27.6%) were initially managed in the CoE and 445 (72.4%) were only presented at the CoE-MDT. Patients in the CoE group more often had intestinal or pancreatic primaries, metastatic disease (61.8% vs 33%), hereditary syndrome, and a functioning tumour. Work-up conformity was 37.1% in the CoE (vs 29.9%, P   = 0.09); this was 95.8% for the first treatment (vs 88.7%, P   = 0.01). After multivariate analysis, CPG conformity was significantly higher for patients managed in the CoE, for younger patients, for those having a grade 1–2 tumour, and a genetic syndrome. Pancreatic and small intestinal (SI) NET surgeries performed in the CoE had a higher splenic preservation rate during left pancreatectomy, better detection of multiple tumours in SI surgeries, and higher number of resected lymph nodes. Conclusions: Given the widespread observance of CPG, not all patients require management in the CoE. Referral should be considered for more complex cases such as metastatic diseases, G2 tumours, or carcinoid syndromes. Finally, we should encourage the centralization of NET surgery.